Pengurangan Nilai COD pada Effluent Fermentor Biogas UASB-HCPB dengan Memanfaatkan Mikroalga Chlorella vulgaris - Sidabutar, Rivaldi; Trisakti, Bambang; Irvan; Bani, Okta; Nasution, Juan Akmal (Jurnal Teknik Kimia USU, 2024)
Palm oil mill effluent (POME) is the main waste generated from the palm oil industry. LCPKS has a COD level of 57,000-60,400 mg/L. High levels of COD can harm the environment. LCPKS treatment techniques generally use a combination of anaerobic and aerobic waste treatment methods. The anaerobic process has been conducted using a UASB-HCPB reactor. But, the COD levels of anaerobic results have not reached the quality standards so that further processing is needed. Microalgae have the potential to reduce contaminant levels in wastewater. Chlorella vulgaris microalgae is a microalgae that is widely used in wastewater treatment. This study utilized Chorella vulgaris in reducing the COD levels of the effluent of the UASB-HCPB biogas fermentor with variations in lighting intensity and variations in the ratio of effluent to microalgae. It was found that the lighting intensity of light:dark (24:0) hours provided optimal microalgae growth so as to provide the best COD reduction with a COD reduction efficiency of 87.5%. The ratio of microalgae to effluent of 1000 mL: 500 mL showed the best COD reduction with an efficiency of 93.75%.